How Streaming Music Reduced Audio Piracy - Magdalena Szczyrba (Future Science / FSH-PH Publications, 2026)
The article traces the evolution of digital music distribution from the era of physical piracy to contemporary legal streaming models. It situates this transformation within the broader framework of Industry 4.0 and the sharing economy highlighting how technological change, widespread connectivity, and new organizational models have reshaped relations between creators, intermediaries, and users. The study reviews key stages of online piracy, including BBS systems, FTP, peer-to-peer networks such as Napster, and digital music stores, and then examines the emergence of streaming platforms like Spotify as a disruptive innovation in access-based music consumption. Particular attention is paid to subscription and freemium models, algorithmic personalization, and the shift from owning files to on-demand streaming, which together significantly reduced the profitability and appeal of illegal music exchange. The article concludes that streaming services have become one of the most effective instruments in curbing music piracy.